2014
DOI: 10.1016/j.econedurev.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The effects of early tracking on student performance: Evidence from a school reform in Bavaria

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 46 publications
1
25
0
5
Order By: Relevance
“…As of 2000, students were stratified into three rather than two tracks based on their previous performance in primary school. In coherence with the theoretical predictions, Piopiunik (2014) concludes that further tracking gave rise to lower state PISA-test scores based on a state-level difference-in-difference research design. However, in his framework, there might be self-selection in or out of the untreated third track which would bias the results.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…As of 2000, students were stratified into three rather than two tracks based on their previous performance in primary school. In coherence with the theoretical predictions, Piopiunik (2014) concludes that further tracking gave rise to lower state PISA-test scores based on a state-level difference-in-difference research design. However, in his framework, there might be self-selection in or out of the untreated third track which would bias the results.…”
Section: Introductionsupporting
confidence: 65%
“…In order to address these problems, randomized experiments appear to be more suitable in precluding self-selection effects. Piopiunik (2014) relied on such a quasi-experimental research design in Bavaria. As of 2000, students were stratified into three rather than two tracks based on their previous performance in primary school.…”
Section: Introductionmentioning
confidence: 99%
“…The low upward mobility in education in Austria can be attributed in part to the national education system, and in particular to its early tracking approach, where the resources and level of educational attainment at home assert a stronger influence than they do in education systems with tracking at a later stage (Betts, 2011;Hanushek, Woessmann, 2005;Brunello, Checchi, 2007;Piopiunik, 2014). Young people from families with a low level of education (parents without a secondary school qualification) in Austria rarely achieve upward mobility in educational attainment: only one in ten members of this group attains a higher education qualification, compared to an OECD average of one in five (OECD, 2015).…”
Section: Baseline Situation and Background Theorymentioning
confidence: 99%
“…However, not all studies had this result (Waldinger, ). Studies that investigated educational reform of tracking practices also found that early tracking increases inequality in academic performance (Hall, ; Jakubowski, Patrinos, Porta, & Wiśniewski, ; Kerr, Pekkarinen, & Uusitalo, ; Malamud & Pop‐Eleches, ; Piopiunik, ). Hence, early tracking increases inequality in academic performance.…”
Section: Introductionmentioning
confidence: 99%